2001
DOI: 10.4315/0362-028x-64.6.885
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effects of Corn Zein Films Impregnated with Nisin, Lauric Acid, and EDTA

Abstract: Bacterial growth during food transport and storage is a problem that may be addressed with packaging materials that release antimicrobials during food contact. In a series of five experiments, EDTA, lauric acid (LA), nisin, and combinations of the three antimicrobial agents were incorporated into a corn zein film and exposed to broth cultures of Listeria monocytogenes and Salmonella Enteritidis for 48 h (sampled at 2, 4, 8, 12, 24, and 48 h). Four experiments used starting cultures of 10(8) CFU/ml in separate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(73 citation statements)
references
References 12 publications
2
69
0
2
Order By: Relevance
“…In contrast, blend film making with the potent antimicrobial fatty acid LAU gave films with the highest antimicrobial activity. This result was quite expected, since Hoffman et al 43 previously showed the high antimicrobial activity of LAUcontaining zein films against L. monocytogenes. Although the results of this work did not indicate antilisterial activity originated from OLE and LIN in zein films, the OLE and LIN solubilized properly in broth medium were reported to have a limited antimicrobial activity on L. monocytogenes.…”
Section: Journal Of Agricultural and Food Chemistrysupporting
confidence: 70%
“…In contrast, blend film making with the potent antimicrobial fatty acid LAU gave films with the highest antimicrobial activity. This result was quite expected, since Hoffman et al 43 previously showed the high antimicrobial activity of LAUcontaining zein films against L. monocytogenes. Although the results of this work did not indicate antilisterial activity originated from OLE and LIN in zein films, the OLE and LIN solubilized properly in broth medium were reported to have a limited antimicrobial activity on L. monocytogenes.…”
Section: Journal Of Agricultural and Food Chemistrysupporting
confidence: 70%
“…Their results showed that L. monocytogenes cell numbers decreased by greater than 4 logs after 48 h of exposure to films containing Lauric acid or nisin alone. 23 The study carried out by Cleveland and colleagues in 2001 have proved that bacteriocins are safe, natural antimicrobials and can be used for food preservation. 12 Mauriello and colleagues developed active polythene films antilisterial film by using the bacteriocin produced by L. curvatus.…”
Section: Effectiveness Of the Package Materials Coated With Bacteriocinmentioning
confidence: 99%
“…A adição de nisina e lisozima em filmes de zeína de milho ou proteína de soja auxiliaram no controle do desenvolvimento de Escherichia coli, Lactobacillus plantarum e Listeria monocytogenes em produtos cárneos (HOFFMAN et al, 2001). Os filmes contribuíram também para reduzir a oxidação lipídica e off-flavors em embalagens de costeletas de carne suína pré-cozidas, prolongando o shelf life durante o armazenamento (CUTTER, 2006).…”
Section: Formas De Extração De Zeína Do Milhounclassified